Taxonomic revision of the freshwater crab genera Travancoriana Bott, 1969, and Vanni Bahir & Yeo, 2007 (Crustacea: Decapoda: Gecarcinucidae), with descriptions of eight new genera and two new species from the Western Ghats, southern India - Pati, Sameer Kumar (Zootaxa, 2025)
The gecarcinucid freshwater crab genera, Travancoriana Bott, 1969, and Vanni Bahir & Yeo, 2007, are known thus far only from the states of Karnataka, Kerala, and Tamil Nadu in southern India, with their species occurring exclusively in the Western Ghats. The taxonomy of these genera is revised using a morphological approach, partly supported by a preceding molecular study, which proved that both genera are polyphyletic, while some species of Vanni s. lat. fit the generic definition of Travancoriana s. lat. In this revision, Travancoriana is restricted to its type species, T. schirnerae Bott, 1969. Five species previously known in Travancoriana are assigned to four new genera: T. charu Bahir & Yeo, 2007 (type species herein designated) and T. pollicaris (Alcock, 1909) to Ponmudiana gen. nov.; T. convexa (Roux, 1931) to Palaniana gen. nov.; T. granulata Pati & Sharma, 2013, to Anamudiana gen. nov.; and T. kuleera Bahir & Yeo, 2007, to Naduganiana gen. nov. The present revision recognises Vanni as comprising four species, including a new species: V. ashini Bahir & Yeo, 2007, V. deepta Bahir & Yeo, 2007, V. gracilis sp. nov., and V. travancorica (Henderson, 1913) (type species). Four species formerly in Vanni are transferred to four new genera: V. giri Bahir & Yeo, 2007, to Idukkiana gen. nov.; V. malabarica (Henderson, 1912) to Santanusus gen. nov.; V. nilgiriensis (Roux, 1931) to Nilgiriana gen. nov.; and V. pusilla (Roux, 1931) to Pusillosa gen. nov., with the designation of a lectotype. Nilgiriana gen. nov. also contains a new species, Nilgiriana paloti sp. nov., described herein. Identification keys are furnished for the known species of Ponmudiana gen. nov., Vanni, and Nilgiriana gen. nov., as well as for the freshwater crab genera of southern India and/or the Western Ghats. Furthermore, a checklist of freshwater crabs of southern India and/or the Western Ghats is provided, which includes their distribution. This study recognises eight new genera and two new species of freshwater crabs, contributing to a better understanding of the diversity and distribution of these important decapod crustaceans, and highlighting the need for continued research into their taxonomy.